Pentingnya Produk Halal di Indonesia: Analisis Kesadaran Konsumen, Tantangan Dan Peluang - Maulizah, Rizlah; Sugianto, Sugianto (Yayasan Abdurrauf Cendekia Nusantara, 2024)
The demand for halal products has forced the industry to adapt. Many large companies have now started producing and certifying their products as halal to attract Muslim consumers. This study aims to analyze consumer awareness of halal products in Indonesia. Halal products have become the main focus in the Indonesian consumer market, which is the country with the largest Muslim population in the world. This research is qualitative in nature and uses a literature study (literature review) and a descriptive analysis approach. The author collects data and information about the subject from various secondary sources, such as journals, reports and web information, then processes and develops the data to make appropriate conclusions about the subject. The research results show that Indonesian consumers' awareness of halal products is increasing rapidly thanks to strict certification and easy access to information through mass media and the internet. The halal lifestyle trend is also becoming popular globally, including in non-Muslim countries. However, certification and regulatory challenges still exist, especially for MSMEs to compete in the global market. Keywords: Consumer Awareness, Halal Products, Indonesia Abstrak: Permintaan akan produk halal telah memaksa industri untuk menyesuaikan diri. Banyak perusahaan besar kini mulai memproduksi dan menyertifikasi produk mereka sebagai halal untuk menarik konsumen Muslim. Studi ini bertujuan untuk menganalisis kesadarn konsumen terhadap produk halal di Indonesia. Produk halal telah menjadi fokus utama dalam pasar konsumen Indonesia, yang merupakan negara dengan populasi Muslim terbesar di dunia. Penelitian ini bersifat kualitaif dan menggunakan studi kepustakaan (review literatur) dan pendekatan analisis deskriptif. Penulis mengumpulkan data dan informasi tentang subjek dari berbagai sumber sekunder, seperti jurnal, laporan, dan informasi web, kemudian mengolah dan mengembangkan data tersebut untuk membuat kesimpulan yang tepat tentang subjek. Hasil penelitian menunjukkan bahwa Kesadaran konsumen Indonesia terhadap produk halal meningkat pesat berkat sertifikasi yang ketat dan akses informasi yang mudah melalui media massa dan internet. Tren gaya hidup halal juga menjadi populer secara global, termasuk di negara-negara non-Muslim. Namun, tantangan sertifikasi dan regulasi masih ada, terutama bagi UMKM untuk bersaing di pasar global